Exploring the Challenges of SDGs Localisation by Rural Local Government Institutions in Bangladesh: A Policy Implementation Perspective - Zahid, Aaqib (Social Science Review, 2023)
The Sustainable Development Goals (SDGs) are a master plan to achieve a sustainable future by 2030, and the government of Bangladesh has been working relentlessly to achieve its targets. Since each country is supposed to take ownership of the goals and tailor policies according to their needs, in the localisation process of the SDGs, the local government institutions play a significant role in implementation. Similarly, in Bangladesh, Rural Local Government Institutions (RLGIs) are likely to play an essential role in the localisation of the SDGs, since they remain close to the most marginalized and often vulnerable rural people and can impact them directly. However, the RLGIs have not made a notable contribution in the localisation of the SDGs so far, and the deadline is approaching. This paper aims to understand the limitation of localising the SDGs by the RLGIs in Bangladesh by exploring the challenges they face that lead to policy implementation failure. From qualitative data collected from six different RLGIs, the paper finds that RLGIs suffer from four broad challenges: financial, political and administrative, behavioural and planning challenges that are causing SDGs localisation implementation failure. The paper concludes that these issues are unlikely to be overcome in a short time, so the future of SDGs localisation within the given timeframe is questionable. Social Science Review, Vol. 39(3), Dec 2022 Page 93-111